1987
DOI: 10.1094/phyto-77-418
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pectolytic Strains ofXanthomonas campestriswith Soft Rots of Fruits and Vegetables at Retail Markets

Abstract: We thank J. E. Butterfield and R. Oseredczuk for help in collecting plant specimens and preparing culture media, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…Th erefore they are generally more susceptible to infection by natural pathogens or even to attack by bacteria that normally do not cause diseases of plants growing in the fi eld (Liao and Wells 1987). King and Bolin (1989) indicated the increase of microbial populations of lettuce under storage conditions which makes our results surprising since we found that the spectrum of identifi ed bacterial pathogens was lower in the second sampling than in the fi rst one.…”
Section: Discussionmentioning
confidence: 60%
“…Th erefore they are generally more susceptible to infection by natural pathogens or even to attack by bacteria that normally do not cause diseases of plants growing in the fi eld (Liao and Wells 1987). King and Bolin (1989) indicated the increase of microbial populations of lettuce under storage conditions which makes our results surprising since we found that the spectrum of identifi ed bacterial pathogens was lower in the second sampling than in the fi rst one.…”
Section: Discussionmentioning
confidence: 60%
“…oryzae (Wakimoto, 1960;Goto, 1965). The early Xpl0 genes are transcribed by the host polymerase, whereas the late Xpl0 genes are transcribed by the Xpl0 RNA polymerase (Liao and Kuo, 1986;Liao et al, 1987). Their host range is restricted to X. o. pv.…”
Section: Phagesmentioning
confidence: 99%
“…vesicatoria induce soft rot symptoms and cause problems on postharvest vegetables and fruits. These pathogenic bacteria are capable of producing pectolytic enzymes and causing maceration of potato tubers and green pepper (Starr and Nasuno, 1967;Liao and Wells, 1987;Beaulieu et al, 1991). The cotton blight pathogen, X. campestris pv.…”
Section: Introductionmentioning
confidence: 99%